Distributed Acoustic Sensing (DAS) for Natural Microseismicity Studies: A Case Study From Antarctica. Issue 7 (16th July 2021) - Hudson, T. S.; Baird, A. F.; Kendall, J. M.; Kufner, S. K.; Brisbourne, A. M.; Smith, A. M.; Butcher, A.; Chalari, A.; Clarke, A.
Abstract: Icequakes, microseismic earthquakes at glaciers, offer insights into the dynamics of ice sheets. For the first time in the Antarctic, we explore the use of fiber optic cables as Distributed Acoustic Sensors (DAS) as a new approach for monitoring basal icequakes. We present the use of DAS for studying icequakes as a case study for the application of DAS to microseismic datasets in other geological settings. Fiber was deployed on the ice surface at Rutford Ice Stream in two different configurations. We compare the performance of DAS with a conventional geophone network for: microseismic detection and location; resolving source and noise spectra; source mechanism inversion; and measuring anisotropic shear‐wave splitting parameters. Both DAS array geometries detect fewer events than the geophone array. However, DAS is superior to geophones for recording the microseism signal, suggesting the applicability of DAS for ambient noise interferometry. We also present the first full‐waveform source mechanism inversions using DAS anywhere, successfully showing the horizontal stick‐slip nature of the icequakes. In addition, we develop an approach to use a 2D DAS array geometry as an effective multi‐component sensor capable of accurately characterizing shear‐wave splitting due to the anisotropic ice fabric. Although our observations originate from a glacial environment, the methodology and implications of this work are relevant for employing DAS in other microseismic environments. Plain Language Summary: Icequakes are like small earthquakes but are caused by the movement of ice rather than two plates sliding past one another. They allow us to investigate glacier processes. For the first time in the Antarctic, we use lasers fired down fiber optic cables to detect and analyze icequake signals. This technique is called Distributed Acoustic Sensing (DAS). These fiber optic cables were laid on the surface of Rutford Ice Stream, Antarctica, in two different shapes. We compare the performance of DAS to conventional geophones for icequake detection and location, investigating the frequency of the earthquake source, investigating the physics that generates the icequake, and the effect of the ice fabric on the travel of seismic waves through ice. For our experiment, DAS is not as good as conventional geophones for detecting icequakes. However, DAS is better than geophones for looking at the frequency of an icequake and the physics that causes an icequake. It also allows us to investigate ice fabric properties in a similar way to geophones. Although our results are for icequakes at a glacier, the methods we use and our findings are relevant for using DAS in many other environments where small earthquakes occur. Key Points: Distributed acoustic sensing can outperform geophones for source spectra and full‐waveform source mechanism inversion 2D distributed acoustic sensing array geometries can be used as a multi‐component sensor capable of measuring shear‐wave splitting Larger surface distributed acoustic sensing deployments and/or hybrid networks are required for accurate microseismic detection/location